2020
DOI: 10.1021/acs.analchem.0c02735
|View full text |Cite
|
Sign up to set email alerts
|

Toward Rapid Screening of Liver Grafts at the Operating Room Using Mid-infrared Spectroscopy

Abstract: The estimation of steatosis in a liver graft is mandatory prior to liver transplantation, as the risk of graft failure increases with the level of infiltrated fat. However, the assessment of liver steatosis before transplantation is typically based on a qualitative or semiquantitative characterization by visual inspection and palpation and histological analysis. Thus, there is an unmet need for transplantation surgeons to have access to a diagnostic tool enabling an in situ fast classification of grafts prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Previous results have shown that the performance of ATR-FTIR methods for steatosis quantification can be improved using dry films to increase the concentration of biomolecules and avoid the intense contribution of water in the mid-IR region. 21 The ATR spectra of dry films showed significant spectral contributions from proteins, carbohydrates, phospholipids, DNA and RNA, and lipids, in agreement with previous reports. Among others, protein bands at 1650 cm −1 (amide I), 1547 cm −1 (amide II), and 1309 cm −1 (amide III), 28 and lipid bands at 1749 cm −1 (saturated ester CO stretching from lipids and cholesterol esters), 1456 cm −1 (CH 2 bending of acyl chains), and 1402 cm −1 (COO– symmetric stretching of fatty acids and amino acids) were identified in the samples.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Previous results have shown that the performance of ATR-FTIR methods for steatosis quantification can be improved using dry films to increase the concentration of biomolecules and avoid the intense contribution of water in the mid-IR region. 21 The ATR spectra of dry films showed significant spectral contributions from proteins, carbohydrates, phospholipids, DNA and RNA, and lipids, in agreement with previous reports. Among others, protein bands at 1650 cm −1 (amide I), 1547 cm −1 (amide II), and 1309 cm −1 (amide III), 28 and lipid bands at 1749 cm −1 (saturated ester CO stretching from lipids and cholesterol esters), 1456 cm −1 (CH 2 bending of acyl chains), and 1402 cm −1 (COO– symmetric stretching of fatty acids and amino acids) were identified in the samples.…”
Section: Resultssupporting
confidence: 92%
“…Recent research on using IR spectroscopy to analyze liver tissue directly has shown that it could be used as a real-time tool to quantify steatosis. 10,19–21 Preliminary results from pilot studies have been positively correlated with qualitative results from histopathology evaluations and off-line biochemical analysis of triglyceride contents. 21 These results indicate that IR spectroscopy could be a valuable tool for the rapid assessment of the grade of steatosis in donated livers, prior to explantation, and provide information about the fat content and overall composition of livers in terms of their proteins, lipids, and phospholipids.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Frozen liver tissue (15−20 mg) was mixed with 450 μL of water in a 2 mL polypropylene tube for tissue homogenization using CK14 ceramic beads (Precellys, France) (two homogenization cycles of 25 s, 6000 rpm, 5 °C) in a Precellys 24 Dualsystem. Hepatic triglycerides isolation was carried out as previously described [ 23 ]. A colorimetric kit (Spinreact, Barcelona, Spain) was employed to analyze total hepatic triglyceride content.…”
Section: Methodsmentioning
confidence: 99%
“…Homogenates from human livers were extracted with a methanol-chloroform mixture and evaporated under nitrogen as described elsewhere [ 36 ]. TG and total lipid concentrations were measured in the lipid residue using colorimetric kits from Spinreact (Gerona, Spain) based on the GPO-POD enzymatic method (#1001311) and the sulfo-phospo-vanillin reaction (#1001270), respectively.…”
Section: Methodsmentioning
confidence: 99%